Analyzing long and short-run relationships between complex gold and silver futures - Pipattadanukul, W. (2015)
The objective of this research was to study the relationship between gold and silver futures in COMEX market by using daily data from 6th of May, 1991 to 6th of May, 2011. There were 5520 observations. To investigate the short run and long run relationships between gold and silver futures price, this study employed unit root test, co-integration test and error correction model. If there are short-run and long-run relationships between gold and silver futures prices, it implied that gold can be used as a predictor to forecast the silver as well. It will provide an opportunity to market participants, investors, hedgers, arbitragers and speculators. The traders can use this relation between gold and silver futures price as trading strategy in order to diversify risk in the portfolio. Speculators can use this information to predict returns and make the investment strategies. Hedgers can use these markets as substitutes against the similar type of risks in a period of time. The empirical results revealed that there is a robust positive relationship between gold and silver future prices in the long run. For the short run relationship, change in the silver futures price significantly affects the gold futures price and vice versa.